Genetic polyandry and sexual conflict in the sandbar shark, Carcharhinus plumbeus, in the western North Atlantic and Gulf of Mexico - PORTNOY, DAVID S; PIERCY, ANDREW N; MUSICK, JOHN A; BURGESS, GEORGE H; GRAVES, JOHN E (Molecular ecology, 2007)
To investigate patterns of polyandry in the sandbar shark (Carcharhinus plumbeus), 20 pregnant females were sampled from the western North Atlantic and Gulf of Mexico. Five species-specific microsatellite markers were used to genotype each shark and its litter. Of 20 litters, 17 (85%) were shown to have multiple sires. In multiply sired litters, the estimated minimum number of sires ranged from two to five with an average of 2.3 males per litter. Regression analysis did not demonstrate a significant relationship between female reproductive success and female body size or sire number and female body size. There was a high incidence of reproductive skew noted in litters, and two groups of males with significantly different mean reproductive success were observed. Analyses using Bateman's principles suggest that there is less direct benefit for females that acquire multiple mates than for males who bias paternity within litters. In light of past morphological and behavioural studies, these data suggest that patterns of polyandry in elasmobranchs may be determined by coercive mating, and that breeding behaviour has likely evolved in the context of sexual conflict.